Profil Electroencephalogram (EEG) Pasien Rumah Sakit Angkatan Laut Dr. Ramelan Surabaya Periode Januari 2018 sampai Desember 2018 - NI KOMANG SRI DWI UTAMI; ERIC HARTONO; WIENTA DIARSVITRI (HANG TUAH MEDICAL JOURNAL, 2019)
ABSTRACT An electroencephalogram (EEG) is an accepted method in neurophysiology with a wide application. Different types of brain rhythms indicate that simultaneous activity of the brain cortex neurons depend on the person’s mental state. Aim: to know the EEG pattern of patients at dr. Ramelan Naval Hospital Surabaya. Method: this research is a descriptive research with prevalence study method. Using total population for sampling, all patients who did the electroencephalogram examination at dr. Ramelan Naval Hospital Surabaya period January 2018 until December 2018. Result:Toddlers were the most frequently patients who did electroencephalogram examination. Based on sex, male were the most frequent. Based on clinical diagnose, patient with convulsive epilepsy are the most frequent with SW wave result